Enhancing Student Class Engagement by Improving Students’ Self-efficacy and Motivation through Organizational Development Interventions - A Case Study of Zhejiang Yuexiu University of Foreign Languages in China - Huang, Ting (ABAC ODI JOURNAL Vision. Action. Outcome, 2020)
This paper aims to study the impact of organizational development interventions on self-efficacy and motivation, so as to enhance student class engagement. The relationship of self-efficacy and motivation on student class engagement is the foundation of the conceptual framework of this study. Social skills, cognitive operation, affective coping, integrative motivation and instrumental motivation will be used as sub-variables to measure the dependent variable of student class engagement (cognitive engagement, emotional engagement and behavioral engagement). The paper uses action research as a research method and non-randomized control group and experimental group are used for comparison. In addition, quantitative and qualitative data are used to measure and analyze the effects on student class engagement, self-efficacy and motivation before and after the organizational development intervention. The results of post-ODI stage shows that the experimental group improved significantly in four variables (social skills, cognitive operation, affective coping, and integrative motivation), and there is a positive correlation between self-efficacy (social skills, cognitive operation, and affective coping) and motivation (integrative motivation) on student class engagement, while the instrumental motivation remained basically unchanged. There is no significant improvement for the control group between pre-ODI and post-ODI stages without any interventions. The implication of this study is that self-efficacy and motivation can be used to improve student class engagement, and in order to achieve sustainable change, further actions should be carry out to have a greater impact on the long-term development